2017
DOI: 10.15274/tpj.2017.02.02.21
|View full text |Cite
|
Sign up to set email alerts
|

Mangroves of Maputo, Mozambique: from Threatened to Thriving?

Abstract: Coastal wetlands worldwide are among the most productive yet highly threatened systems in the world, and are framed and protected by the Convention on Wetlands (Ramsar, Iran, 1971), of which Mozambique is a party since 2004 (IUCN, 1971). Maputo city coastline consists of an ample alluvial plane, where large extensions of mangrove forests occur within the city, namely the Costa do Sol wetlands, offering a wide range of ecological and economical services. Here, urban development pressure is increasing and rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Machangulo Peninsula, Maputo province) as having a high potential for mangrove forests occurrence. Although, this region is currently dominated by sand dunes (Bandeira and Paula, 2014) and coastal lakes and lagoons (da Costa and Ribeiro, 2017), other studies performed in the Amazon Coast of Brazil (see Costa et al, 2016) revealed a high rate of survival and growth of mangrove seedling survival on sandy soils. Excluding estuaries, coastal Mozambique has rather sandy sediments; the sand dunes dominating the long stretch of southern Mozambique, and also South Africa (Kwazulu/Natal) (Tinley, 1985) are potentially favourable for mangrove recolonization provided that a conducive condition exists, such as regular tidal flooding (Spier et al 2016).…”
Section: Suitable Areas For the Occurrence Of Mangrove Speciesmentioning
confidence: 98%
“…Machangulo Peninsula, Maputo province) as having a high potential for mangrove forests occurrence. Although, this region is currently dominated by sand dunes (Bandeira and Paula, 2014) and coastal lakes and lagoons (da Costa and Ribeiro, 2017), other studies performed in the Amazon Coast of Brazil (see Costa et al, 2016) revealed a high rate of survival and growth of mangrove seedling survival on sandy soils. Excluding estuaries, coastal Mozambique has rather sandy sediments; the sand dunes dominating the long stretch of southern Mozambique, and also South Africa (Kwazulu/Natal) (Tinley, 1985) are potentially favourable for mangrove recolonization provided that a conducive condition exists, such as regular tidal flooding (Spier et al 2016).…”
Section: Suitable Areas For the Occurrence Of Mangrove Speciesmentioning
confidence: 98%